Resistance and Representation in Amharic Folk Poetry (1889-1974) - Mengistu, Melakneh (Cultural and religious studies, 2018)
Amharic folk literature is a time-honoured tradition dating back to the imperial songs of the 14th and 15th centuries. One of these subgenres is Amharic folk poetry which is permeated with the political, social, economic, and cultural legacies of successive Ethiopian governments that rise and demise. The image of these governments was determined by their integrity, vision, and responsiveness to the aspirations of the populace. This study was designed to determine the popular image of the imperial governments of Menelik II and Haile Selasse I as reflected in Amharic folk poetry. Without prejudice to some odes which invariably idealise the vision of these monarchs, the politically-inspired Amharic folk poetry is found to be critical of the feudal status quo thus perpetuating its negative images. This underpins the partial unpopularity of Menilik and Haile Selasse. However, these critical gestures would by no means undermine their monumental contributions to the reunification, modernization, and survival of Ethiopia. Thus, the contemporary Amharic folk-poetry is neither iconoclastic nor idealistic but an impassioned allegory of the nation-state.